Safety and health management commitment in Fire and Rescue Department, Kuala Lumpur, Malaysia - Askari, Arameh (2017)
High-risk organizations are continuously trying to minimize risks. There is a developing concern about safety and health at work, until 1994, but Malaysia still did not have adequate provisions for safety and health of employees at the work environment, while technology and high standards are crucial, a core aspect of an effective health and safety management system constitutes the main theme for this study. In order to determine the state of safety commitment of an organization; 5 element of policy, organizing, evaluation, planning and implementation and action for improvement were measured through quantitative studies. With a specific end goal to gather required data about OSH Management System, proper questionnaire has been utilized to look for the present commitment of employers and employees. The total number of respondents for measuring a commitment were 347. For approaching a fire safety model one more set of designed questionnaire were answered by 309 respondents with higher level of education. The analytical technique is utilized to demonstrate the outcome by analyze the primary and essential information which is obtained from questionnaires. The sorts of analysis required for each of the research objectives is Kruskal Wallis for measuring the commitment of 5 elements of OSH management system, TOPSIS method for ranking the 5 elements of OSH management system, percentage descriptive analysis to identified the type of hazards, and ANOVA one way for determination of level of awareness, and the developed model were tested by LISREL software and the adequacy of the structure were validating by KMO test. The results from the related questionnaire (measuring commitment of 5 elements) showed that in policy part all stations showed high commitment which Chi square shows 58.152, in comparing the commitment of stations station Hang Tuah were committed in all part of elements while station Kepong only had higher level of commitment base on the mean rank (180.66) in comparison with the Hang Tuah station. The results for ranking the 5 elements showed that evaluation with weight 2.810 is the most important factor. Findings indicate that all of the concerns identified elements are linked to commitment. To achieve the level of the awareness of the workers the descriptive analysis was applied. The results showed that the level of the awareness among the workers are high with mean rank of 3.95. Regarding the type of the hazards of the department, fire explosion indicates a problematic hazard in the Fire and Rescue Department in Kuala Lumpur city. Therefore, the safety model was developed. A research additionally could build the information on relevant divisions like Bomba, which can support the businesses, worker, authorities and related organizations to put more efforts in regulating and handling the safety and health systems. The information presented in this study are essential since they give firm evidence of safety and health management which is useful for future references.